METODE PENAFSIRAN AL-ZUHAYLî DALAM AL-TAFSîR AL-MUNîR - Ainol, Ainol (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2011)
The first and the foremost authority interprets the Koran is the Prophet Muhammad because he was receiving a direct Koran. After the Prophet, the authority was followed by his companions, tâbi?în, and mufassir afterward. Interpretations performed above the companions known as tafsîr bi al-ma?thur. This commentary underlies the discussion and its source in history. This method became known as a method of interpretation of the Koran is called the method of history. In addition, the method used at that time was the tafsîr bi al-ra?y underlying source on reasoning and ijtihâd. One contemporary commentator who try to combine the two sources of the interpretation is Wahbah al-Zuhaylî. The interpretation of the content approached the Koran, from a classic interpretation that many make al-ma?thur as the source and from the angle of the many modern and contemporary make ra?y as the source